(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
This article documents the implementation of a community service programme facilitating the Kampung Deret initiative in Tanah Tinggi Urban Village, Central Jakarta, as one of the first instances of Vertical Land Consolidation (VLC) in Indonesia. Through a participatory design approach, eight informal settlement plots were consolidated into a single four-storey residential building comprising twelve dwelling units, shared communal spaces, a commercial unit, and supporting facilities. As architect-facilitators, the implementation team conducted a structured series of socialization sessions, community deliberations (rembug warga), and Development Rights-based agreement formulation, whereby land and building ownership rights were converted into proportional dwelling unit entitlements within a multi-family structure, legally equivalent to the conversion of individual freehold title (SHM) into strata title (SHMSRS) under Law No. 16 of 1985 on Flats. The facilitation programme achieved all four designated performance indicators: (1) a unit distribution agreement signed by all Prospective Residents/Beneficiaries (PRBs); (2) a building design concept meeting Healthy Home (Rumah Sehat) parameters and endorsed by the PRBs; (3) completion of a Detailed Engineering Design (DED) document; and (4) physical construction of the Kampung Deret Tanah Tinggi building, which expanded residential capacity from eight to eleven units distributed to PRBs, with one additional communal unit designated as a building maintenance revenue source. This article contributes to the development of a replicable VLC model for addressing urban informal settlements in Indonesia, emphasizing community preparation, transparency of rights distribution mechanisms, and flexibility in accommodating individual needs as prerequisite conditions for programme success.